Pelamonia: Sejarah Rumah Sakit Militer Peninggalan Kolonial di Jantung Kota Makassar (1986-2012) - Kabubu, Rusmala Dewi; Malihu, La (Universitas Negeri Gorontalo, 2025)
The Dutch established a health facility in 1917 called the Militaire Hospital. After the Dutch government recognized Indonesia's sovereignty, the hospital was transferred to the Indonesian government and began operating under the direct management of the military. The hospital's name was changed multiple times due to changes in the military, particularly in the Army, until it was officially named Pelamonia Hospital. This paper examines the development of military health institutions and their dual role in interacting with civil society. This research uses the historical method to reconstruct, explain, and understand past events. The development of this hospital began in 1986 with the inauguration of a new four-story main building, which was the first physical development carried out by Pelamonia Hospital. From 1986 to 2012, the hospital underwent a series of construction projects to address the escalating demand for patient care, attributable to an increase in both military and civilian patients. This hospital plays a dual role in providing health services. In addition to its main task of providing health services for the military, it also opens health services to the general public. Pelamonia Hospital has a positive impact on both the military and the general public, which can be seen from various perspectives, including health, social, economic, and educational ones.